PENGEMBANGAN MODEL PEMBELAJARAN KOLABORATIF SEND A-PROBLEM BERBASIS BBL UNTUK PEMBELAJARAN IPA SMP DI WILAYAH AGROEKOSISTEM - Nabilla Syakhina Yulyatno; Jekti Prihatin; Kamalia Fikri (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2019)
Students in the agroecosystem area have self-motivation to follow low learning which causes their learning outcomes lower. It can be increased by applying Brain-Based Learning (BBL) approach combined with Send A-Problem (SAP) collaborative learning model. This is a development research using 4-D model. Only 3 stages were chosen; define, design, and develop. The research aims to produce a valid, practical and effective SAP based on BBL to increase students' metacognitive awareness and learning outcomes. The average of product validation is 88 (very valid category). The average percentage of students' metacognitive awareness was 66.31 (developing category) before the application and 85.85 (very good category) after the application of the learning. Normalized gain analysis result is 0.62 referred to medium category, which means that there is an increase in student learning outcomes. The average percentage of student (84.33%) and teacher responses (98%) is included in the very practical category.